Didattica inclusiva: aspetti metodologici, epistemologici e percorsi di ricerca - Franceschini, Giuliano (Studi sulla Formazione/Open Journal of Education, 2019)
Inclusive education in international educational research occupies a very important position. However, the meaning of the term inclusion is not always clear. The article explains how to understand the authentic meaning of inclusive education, through the perspective of Disability Studies. In particular, the concept of normative and relative abilities will be compared, and some inclusive educational strategies will be analyzed. Finally, the links between inclusive education and educational research and the influence of J. Dewey's thought in the development of inclusive educational theory and practice will be described.